Laboratory Characteristics And Diagnostic Significance Of Antibiotic-Associated Diarrhea In Young Children (Texas Journal of Medical Science, 2025)
To determine the specific laboratory characteristics of AAD in early childhood and assess the diagnostic value of fecal calprotectin, C-reactive protein (CRP), and coprological parameters in differentiating disease forms.